2017
DOI: 10.1186/s12906-017-1680-9
|View full text |Cite
|
Sign up to set email alerts
|

Buyang Huanwu decoction facilitates neurorehabilitation through an improvement of synaptic plasticity in cerebral ischemic rats

Abstract: BackgroundLoss of neural function is a critical but unsolved issue after cerebral ischemia insult. Neuronal plasticity and remodeling are crucial for recovery of neural functions after brain injury. Buyang Huanwu decoction, which is a classic formula in traditional Chinese medicine, can positively alter synaptic plasticity. This study assessed the effects of Buyang Huanwu decoction in combination with physical exercise on neuronal plasticity in cerebral ischemic rats.MethodsCerebral ischemic rats were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…MAP-2, a protein that was enriched in neuronal dendrites, regulates microtubule dynamics in dendrites and is important for dendritic plasticity. MAP-2 loss has been documented after cerebral ischemic, and therapies that enhanced MAP-2 expression decreased the mortality and neurological impairments of MCAO rats [26]. In our study, declined MAP-2 Immunofluorescence activity was noticed in rats subjected to MCAO modeling, while CY inhibited this decrease and improved the neurological outcomes and pathological changes in MCAO animals, reflecting the essential role of MAP-2 in experimental ischemic stroke and CY-generated therapeutic efficacy.…”
Section: Discussionsupporting
confidence: 58%
“…MAP-2, a protein that was enriched in neuronal dendrites, regulates microtubule dynamics in dendrites and is important for dendritic plasticity. MAP-2 loss has been documented after cerebral ischemic, and therapies that enhanced MAP-2 expression decreased the mortality and neurological impairments of MCAO rats [26]. In our study, declined MAP-2 Immunofluorescence activity was noticed in rats subjected to MCAO modeling, while CY inhibited this decrease and improved the neurological outcomes and pathological changes in MCAO animals, reflecting the essential role of MAP-2 in experimental ischemic stroke and CY-generated therapeutic efficacy.…”
Section: Discussionsupporting
confidence: 58%
“…Taken together, the NF-κB signaling pathway is crucial for the regulation of inflammation following ischemic stroke. It means that suppression of the NF-κB signaling pathway could downregulate inflammation and alleviate I/R injury [49][50][51]. is study has shown that LSZ contribute to the inhibition of proinflammatory cascades following ischemic stroke by suppressing the NF-κB signaling pathway.…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%
“…BHD has been reported to improve ischemic brain injury by reducing glutamate-mediated excitatory amino acid toxicity, resulting in enhanced ATP supply and weakened apoptosis (Wang et al, 2011). At the same time, the improved synaptic ultrastructure by BHD also contributed to the recovery of cerebral ischemia sequelae (Pan et al, 2017). Similarly, ShenGui SanSheng san could also improve the efficiency of citric acid cycle to improve the brain energy deficit after ischemia (Luo et al, 2019).…”
Section: Prescription and Molecular Mechanisms In Regulating Mptp Opementioning
confidence: 99%